ANALISIS PROSES PRODUKSI PROGRAM ACARA TALKSHOW SIARAN LANGSUNG BALI TV SAMATRA ARTIS BALI SEBAGAI WADAH PUBLIKASI KARYA MUSISI LOKAL - Putri, Gracia Gandi Manggala; Irawan, Ricky; Sumerjana, Ketut (MELODIOUS : JOURNAL OF MUSIC, 2024)
The Samatra Artis Bali Talkshow live broadcast program has succeeded in becoming a forum for local musicians to publish their work. Because as a local Balinese television media, Bali TV is a source of information media that is able to instill noble cultural values, as well as supporting local Balinese artists. In accordance with the Merdeka Belajar Kampus Merdeka (MBKM) curriculum, the author had the opportunity to carry out an Internship/Work Practicum program which was carried out on Bali TV. The aim of this research is to explain the production process carried out. This research uses descriptive qualitative research methods with observation techniques on Bali TV. Data collection in preparing this thesis was obtained through interviews, documentation and observation. The author had the opportunity to directly see the pre-production, production and post-production processes. In the research carried out, at the pre-production process stage, the production team held an internal meeting to prepare the rundown. At the production stage, a 1 hour Live On-Air was carried out. And in the post-production stage, the team evaluates whether or not there are any obstacles that occurred during the program. A television program will not run smoothly if the behind-the-scenes activities are not managed effectively. With this thesis, the author hopes that readers, especially the Balinese people, including artists/art lovers, can better appreciate and preserve cultural works of art in Bali. The Bali Artist Samatra Program makes writers understand more about the importance of publishing their work/introducing their work via television media.